1999
DOI: 10.1074/jbc.274.21.15041
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analyses of the ATX1 Metallochaperone

Abstract: Saccharomyces cerevisiae Atx1p represents a member of the family of metallochaperone molecules that escort copper to distinct intracellular targets. Atx1p specifically delivers copper to the Ccc2p copper transporter in the Golgi. Additionally, when overproduced, Atx1p substitutes for superoxide dismutase 1 in preventing oxidative damage; however the mechanistic overlap between these functions is unresolved. The crystal structure of Atx1p has been solved recently. By examining a surface electrostatic potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(132 citation statements)
references
References 33 publications
7
122
0
Order By: Relevance
“…4b, meaningful differences between apo and CuCox17 occur where the rmsd between the two representative structures is greater than the sum of the rmsds of the two ensembles of structures. There are slight differences for coordinating residue Cys 26 and for Met 58 , which is close to the modeled Cu(I) ion (Fig. 4a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4b, meaningful differences between apo and CuCox17 occur where the rmsd between the two representative structures is greater than the sum of the rmsds of the two ensembles of structures. There are slight differences for coordinating residue Cys 26 and for Met 58 , which is close to the modeled Cu(I) ion (Fig. 4a).…”
Section: Resultsmentioning
confidence: 99%
“…This residue, which is essential for function (58), has been proposed to modulate copper transfer (50,52). In the CuCox17 structure, conserved residue Lys 30 is proximal to the copper-binding site and could counterbalance the negative charge because of the presence of three cysteines.…”
Section: Resultsmentioning
confidence: 99%
“…Consideration of the electrostatic properties of each domain furnishes part of the answer. Interactions between Atox1 or Atx1 and their target domains involve complementary electrostatic surfaces (15,16,37,48). In particular, positively charged residues on the chaperone surface interact with negatively charged residues on the target domain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent yeast two-hybrid analyses of the yeast HAH1 homologue, ATX1, showed that mutation of the corresponding residues, Lys 65 3 Glu and Lys 61 3 Glu ϩ Lys 62 3 Glu, as well as other compound lysine to glutamate mutations, abolish interaction between the copper chaperon and CCC2p, the WD/ MNK homologue (35). As the x-ray crystal structures for ATX1p (36) and the fourth metal-binding domain of MNKp (MNK4) have recently been reported (37), we attempted to reconcile these differences by modeling the WDp/MNKp -HAH1p interaction.…”
Section: Yeast Two-hybrid Analysis Of the Wdp Metal-binding Domain Anmentioning
confidence: 99%